NILAI-NILAI HUMANISME DALAM DIALOG ANTAR AGAMA PERSPEKTIF GUS DUR - Aqil, Muhammad (Al-Adyan: Journal of Religious Studies, 2020)
Gus Dur is a humanist figure. This can be seen from his thought on the conflict resolution and the defence of minority rights which he strugles. The humanistic dialogue is a form of the conflict resolution which is offerred.  The basis of the interfaith dialogue that Gus Dur offerred is the concept of religious humanism. This concept rooted in his thoughts on Islamic universalism which tauched the political, economic, and social aspects. There are nine the humanistic values that derrived from the consept of Islamic universalism which become the basis of religious conflict resolution and struggle for the monitity rights, namely: tauhid (monotheism), humanity, equality, liberation, simplicity, brothehood, chivalary, and local wisdom.Gus Dur adalah seorang figur humanis. Hal ini bisa dilihat dari pemikirannya tentang resolusi konflik dan pembelaan hak-hak minoritas yang dia perjuangan. Dialog humanistik merupakan bentuk resolusi konflik yang ditawarkan. Basis dialog antar agama yang Gus Dur tawarkan adalah konsep humanisme agama. konsep ini berakar pada pemikirannya tentang  universalime Islam yang menjadi basis  resolusi konflik agama dan perjuangan hak-hak minoritas, yakni: tauhid, kemanusiaan, persamaan, kebebasan, kesederhanaan, persaudaraan, kesatriaan, dan kearifan lokal.